2008
DOI: 10.1162/jocn.2008.20086
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scenes Improve Recollection and Recall of Words

Abstract: Exploring a novel environment can facilitate subsequent hippocampal long-term potentiation in animals. We report a related behavioral enhancement in humans. In two separate experiments, recollection and free recall, both measures of hippocampus-dependent memory formation, were enhanced for words studied after a 5-min exposure to unrelated novel as opposed to familiar images depicting indoor and outdoor scenes. With functional magnetic resonance imaging, the enhancement was predicted by specific activity patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 33 publications
8
86
4
1
Order By: Relevance
“…A first animal demonstration showed that novelty exploration indeed can facilitate consolidation in subsequent declarative memory formation and lead to improved recall 24 h later (Salvetti et al, 2014). Similar effects of novelty exploration in humans, have so far been reported for immediate memory tests (Fenker et al, 2008;Schomaker et al, 2014). Also in this domain, there is preliminary evidence that transfer in training of some skills may depend on individual differences in prefrontal dopamine availability.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A first animal demonstration showed that novelty exploration indeed can facilitate consolidation in subsequent declarative memory formation and lead to improved recall 24 h later (Salvetti et al, 2014). Similar effects of novelty exploration in humans, have so far been reported for immediate memory tests (Fenker et al, 2008;Schomaker et al, 2014). Also in this domain, there is preliminary evidence that transfer in training of some skills may depend on individual differences in prefrontal dopamine availability.…”
Section: Resultsmentioning
confidence: 67%
“…Importantly, the memory-stabilizing effect of dopamine extends to other information encoded when dopamine is available, a phenomenon also referred to as the 'penumbra hypothesis' (Lisman et al, 2011). The hypothesis predicts that once dopamine availability is enhanced, any encoded information will benefit from preferential consolidation, regardless of the actual trigger of the dopamine release (Lisman et al, 2011), and initial evidence from rodent (Ballarini et al, 2009; and human (Fenker et al, 2008;Wittmann et al, 2011) data points out that it may indeed be so. Boosts in dopamine availability at encoding thus result in memory being more stable and better protected from forgetting, an effect that may predominantly arise at long (>24 h) but not short time intervals after learning, highlighting the role of memory consolidation processes and sleep in dopaminergic modulation of memory traces (See Box 2 on the role of sleep in consolidation; Perogamvros and Schwartz, 2012).…”
Section: Role Of Dopamine In Learning and Memory Consolidationmentioning
confidence: 99%
“…Although it is generally agreed that the hippocampus is critical for both encoding and retrieval (Scoville and Milner, 1957;Eichenbaum et al, 2007; Squire et al, 2007), it remains unknown how the hippocampus supports the complex demands of both processes. However, the unique pattern of afferent projections converging on area CA1, the major hippocampal output subregion, may provide an answer.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the rapid formation of memory traces representing single episodes requires high levels of synaptic plasticity that, during retrieval, could lead to the overwriting of stored memories. Conversely, successful associative retrieval requires that cues reactivate related memory traces and thus benefits from a low threshold for memory reinstatement, but reinstating related memories at the time of encoding could lead to proactive interference (O'Reilly and McClelland, 1994).Although it is generally agreed that the hippocampus is critical for both encoding and retrieval (Scoville and Milner, 1957;Eichenbaum et al, 2007; Squire et al, 2007), it remains unknown how the hippocampus supports the complex demands of both processes. However, the unique pattern of afferent projections converging on area CA1, the major hippocampal output subregion, may provide an answer.…”
mentioning
confidence: 99%
“…Novelty and novel contexts, like reward, engage midbrain modulation of the hippocampus and triggering of VTA activity, and studies again implicate D1/D5 receptors in gating hippocampal long-term plasticity, so enhancing long-term memory for novel events [47]. As with reward uncertainty, novelty may influence tonic dopamine response [59] and may have also implications for theorising learning games, since the effects of novelty on human memory include the types background contextual novelty that are typical in games [79]. Exploring novel environments for words improves memory for them [80] or unrelated novel but educational event [81].…”
Section: Reward and Educational Learning Gamesmentioning
confidence: 98%